Deteksi Rickettsia spp. pada Pinjal Tikus di Kota Semarang - Dyah Widiastuti; Ulfah Farida Trisnawati; Nova Pramestuti (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2018)
Indonesia was reported as endemic area of rickettsiosis, antibody anti Rickettsia typhi has been detected in human population in Jakarta and Semarang. High population of rats in Semarang might contribute to rickettsiosis transmission. Rickettsiosis is caused by Rickettsia spp. which is transmitted by rat ectoparasite. Surveillance system of rickettsiosis in Semarang City has not been established, so the infection of R. typhi in rat flea was under reported. The aim of this study were to identify flea species on rats and to investigate the presence of Rickettsia spp. infection in fleas pool. The fleas were collected from rodent which were captured using single live trap in some areas in Semarang within April-November 2016. Rickettsia spp. DNA of these flea samples were detected by polymerase chain reaction. The result showed that Rattus tanezumi, R. norvegicus, R. exulans, Bandicota indica, B. bengalensis, Mus musculus and Suncus murinus were infested with Xenopsylla cheopis. A total of 144 X. cheopis pools were tested. Fifty (34.7%) pools of X. cheopis were infected with Rickettsia spp. There were no significant correlation between host species and sex toward the infection of Rickettsia spp. in fleas population. High infection rate of Rickettsia spp. among Xenopsylla cheopis population. in Semarang City can play a role in transmission of rickettsiosis. ABSTRAKIndonesia merupakan negara endemis rickettsiosis, di kota-kota besar seperti Jakarta dan Kota Semarang pernah ditemukan adanya antibodi Rickettsia typhi pada manusia. Populasi tikus yang tinggi di Kota Semarang memungkinkan terjadinya penularan rickettsiosis. Rickettsiosis disebabkan oleh Rickettsia spp. yang ditularkan melalui ektoparasit tikus. Sistem surveilans rickettsiosis di Kota Semarang belum ada, sehingga adanya infeksi R. typhi pada pinjal tikus menjadi tidak terlaporkan. Tujuan dari penelitian ini untuk mendeteksi keberadaan R. typhi pada pinjal tikus di Kota Semarang. Pinjal diperoleh dari tikus yang tertangkap dengan metode live trap di beberapa lokasi Kota Semarang pada bulan April-November 2016. DNA Rickettsia spp. dari sampel pinjal dideteksi menggunakan Polymerase Chain Reaction (PCR). Hasil penelitian menunjukkan bahwa Xenopsylla cheopis menginfestasi semua tikus tertangkap yaitu Rattus tanezumi, R. norvegicus, R. exulans, Bandicota indica, B. bengalensis, Mus musculus dan Suncus murinus. Pengujian dengan PCR dilakukan pada sebanyak 144 pool X. cheopis, lima puluh pool sampel X. cheopis (34,7%) positif Rickettsia spp. Tidak ada korelasi yang signifikan antara spesies inang dan jenis kelamin inang terhadap infeksi Rickettsia spp. pada populasi pinjal. Tingginya X. cheopis terinfeksi dengan Rickettsia spp. dapat berpotensi menjadi sumber penularan rickettsiosis di Kota Semarang.